2017
DOI: 10.1038/srep41440
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin protects against early burn-wound progression in rats by attenuating oxidative stress-induced inflammation and mitochondria-related apoptosis

Abstract: Burn-wound progression can occur in the initial or peri-burn area after a deep burn injury. The stasis zone has a higher risk of deterioration mediated by multiple factors but is also considered salvageable. Astaxanthin (ATX), which is extracted from some marine organisms, is a natural compound with a strong antioxidant effect that has been reported to attenuate organ injuries caused by traumatic injuries. Hence, we investigated the potential effects of ATX on preventing early burn-wound progression. A classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 51 publications
2
72
0
8
Order By: Relevance
“…As a ROS scavenger and chemically antioxidant, ATX has two special structures, the polyene chain and terminal ring, which equipped ATX with outstanding antioxidant capacity to capture and scavenge radicals and prevent chain reactions. Meanwhile, ATX has been suggested to improve SOD and glutathione and inhibit the xanthine oxidase and NADPH oxidase, therefore balance the prooxidant and antioxidant [20]. In the present study, oxidant load and poor defensive ability to oxidative stress of VSMCs in the aorta were alleviated by ATX with reduced ROS, more expression of SOD2, and less expression of NOX4 and H 2 O 2 .…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 46%
“…As a ROS scavenger and chemically antioxidant, ATX has two special structures, the polyene chain and terminal ring, which equipped ATX with outstanding antioxidant capacity to capture and scavenge radicals and prevent chain reactions. Meanwhile, ATX has been suggested to improve SOD and glutathione and inhibit the xanthine oxidase and NADPH oxidase, therefore balance the prooxidant and antioxidant [20]. In the present study, oxidant load and poor defensive ability to oxidative stress of VSMCs in the aorta were alleviated by ATX with reduced ROS, more expression of SOD2, and less expression of NOX4 and H 2 O 2 .…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 46%
“…The oral absorbability of ASD was evaluated by measuring the AST concentrations in the serum and liver of ICR mice 0, 3,6,9,12,15,24,48, and 72 h after a single oral dose of ASD (100 mg kg −1 , AST equivalents) in the corn oil vehicle, administered via gavage (Fig. 3a).…”
Section: Metabolism Of Ast and Its Existing Forms In Different Icr Momentioning
confidence: 99%
“…10 Furthermore, AST improves liver function 11 and destroys peroxide chain reactions to protect cells from oxidative damage. 12,13 AST also affects ultraviolet A (UVA) radiation as well as desquamation of the epidermis and the extracellular matrix of the dermis. 14 In addition, it improves heart function 15 by increasing the production of antibodies and T-cells, inflammation and age-related macular degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS lead to skin aging via oxidative damage that are induced by UVR. Therefore, topical formulations which have antioxidant effect could reduce aging level [200]. Eren et.al, 2019 reported that topical formulations of astaxanthin-loaded algae extractcould be suggested as topical anti-aging formulations [199].…”
Section: Astaxanthinmentioning
confidence: 99%
“…Eren et.al, 2019 reported that topical formulations of astaxanthin-loaded algae extractcould be suggested as topical anti-aging formulations [199]. Comparative studies examining the photoprotective effects of carotenoids have demonstrated that astaxanthin is a superior antioxidant, having greater antioxidant capacity than canthaxanthin and β-carotene in human dermal fibroblasts [200].In particular, astaxanthininhibits ROS formation and modulates the expression of oxidative stress-responsive enzymes such as heme oxygenase-1 (HO-1), which is a marker of oxidative stress and a regulatory mechanism involved in the cell adaptation against oxidative damage [205]. Figure 17: The proposed mechanism by which astaxanthin inhibits oxidative stress-induced mitochondrial dysfunction, and development and progression of diseases [211].…”
Section: Astaxanthinmentioning
confidence: 99%